Implementasi Disaster Recovery Center (DRC) di Rumah Sakit XYZ dengan Menggunakan Carbonite Availability: Implementasi Disaster Recovery Center (DRC) di Rumah Sakit XYZ dengan Menggunakan Carbonite Availability - Dinata, Riadi Marta; Dony, Dony; Marhaeni, Marhaeni (JURNAL REKAYASA INFORMASI, 2025)
Disaster Recovery Center (DRC) is a terminology widely recognized by organizations that rely on information technology as their operational foundation, particularly those requiring high availability systems. Hospital institutions that have implemented Hospital Management Information Systems (HMIS) in their administration face significant risks to healthcare service continuity when system disruptions occur. This research aims to analyze the implementation of DRC at XYZ Hospital using Carbonite Availability technology to ensure operational continuity of hospital information systems. The research methodology adapts Hossam’s data center recovery model consisting of three phases: Disaster Recovery Assessment Plan, Disaster Recovery Action, and System/Application Testing & Analysis. Carbonite Availability is an application with block device storage replication technology between servers that enables real-time data synchronization. Test results show that the system can achieve Recovery Time Objective (RTO) of less than 15 minutes and Recovery Point Objective (RPO) approaching zero with 100% failover success rate. DRC implementation proves effective in ensuring hospital information system service continuity with minimal operational disruption and maintaining data integrity during disaster recovery processes. Keywords: disaster recovery center, hospital information system, carbonite availability, business continuity, high availability.